Increased Carotid Siphon Tortuosity Is a Risk Factor for Paraclinoid Aneurysms - Liu, Shilin; Jin, Yu; Wang, Xukou; Zhang, Yang; Jiang, Luwei; Li, Guanqing; Zhao, Xi; Jiang, Tao (Frontiers in Neurology, 2022)
Background: Geometrical factors associated with the surrounding vasculature can affect the risk of aneurysm formation. The aim of this study was to determine the association between carotid siphon curvature and the formation and development of paraclinoid aneurysms of the internal carotid artery. Methods: Digital subtraction angiography (DSA) data from 42 patients with paraclinoid aneurysms (31 with non-aneurysmal contralateral sides) and 42 age- and gender-matched healthy controls were analyzed retrospectively. Morphological characteristics of the carotid siphon (the posterior angle [α], anterior angle [β], and Clinoid@Ophthalmic angle [γ]) were explored via three-dimensional rotational angiography (3D RA) multiplanar reconstruction. The association between carotid siphon morphology and the formation of paraclinoid aneurysms was assessed through univariate analysis. After this, logistic regression analysis was performed to identify independent risk factors for aneurysms. Results: Significantly smaller α, β, and γ angles were reported in the aneurysmal carotid siphon group when compared to the non-aneurysmal contralateral healthy controls. The β angle was best for discriminating between aneurysmal and non-aneurysmal carotid siphons, with an optimal threshold of 18.25°. By adjusting for hypertension, smoking habit, hyperlipidaemia, and diabetes mellitus, logistic regression analysis demonstrated an independent association between the carotid siphons angles α (odds ratio [OR] 0.953; P < 0.05), β (OR 0.690; P < 0.001) and γ (OR 0.958; P < 0.01) with the risk of paraclinoid aneurysms. Conclusions: The present findings provide evidence for the importance of morphological carotid siphon variations and the likelihood of paraclinoid aneurysms. These practical morphological parameters specific to paraclinoid aneurysms are easy to assess and may aid in risk assessment in these patients.